(untitled) (Journal of Engineering, 2006)
In this paper, soil – pore fluid behavior of a silo under an earthquake loading is investigated. To predict the response of the silo with the soil surrounding it, ‘the linear-elastic constitutive model’ is adopted with soil properties; shear modulus and damping ratio; are strains and cycle independent. A computer program using dynamic stiffness matrix analyses (DSMA) for predicting and analyzing the model was established using FORTRAN coding. The program is based on geophysical values (such as primary velocity (vp), shear velocity (vs), modulus of elasticity (E), mass density (), shear modulus (G),….etc). The values were obtained from field test results for the soil under a silo located in Kirkuk, Iraq. To check and compare the obtained results, the computer program (MSC/NASTRAN) is used also for predicting and analyzing the same problem. This second program uses input values such as shear modulus (G), modulus of elasticity (E), mass density () and damping ratio () obtained from conventional laboratory tests. From the two aforementioned analyses, comparisons between the results of the relevant two programs are made. Though program “MSC/NASTRAN” visualizes a realistic behavior of the silo under dynamic loading, due to full response results are expressed for each node, the dynamic stiffness matrix analyses program (DSMA) gives only the maximum value for the horizontal and vertical displacements at that node. Despite of that, program DSMA relies on realistic values of geophysical tests obtained from the field directly.As a conclusion from this study, the soil-structure interaction zone for the silo at Kirkuk under investigation using both analyses show excellent agreement between the results. The agreement in this study turns out to be more than 95% close between the two algorithms. The easiness through which geophysical field tests are conducted, the simplicity of carrying out the required calculations and the reliability of the results makes the dynamic stiffness matrix analysis method (DSMA) highly recommended. It can give an excellent directive about the response of structures resting on soils and subjected to dynamic loads.